Viroinformatic Study of Star Anise (Illicium verum) as Mpro Inhibitor in SARS-CoV-2 Infection - Arianto, Steven; Lakoan, Milda Rianty; Arianti, Varda (Nusantara Science and Technology Proceedings, 2024)
The spread and infection of SARS-CoV-2 towards the end of 2019 started the COVID-19 outbreak. Additionally, the antiviral medications that are still missing. Spices were among the many traditional medicines used in Indonesia. This research aims to find possible bioactive compounds in star anise with antiviral qualities to treat COVID-19 against SARS-CoV-2 proteases through the in-silico approach. Samples were obtained from the Protein Data Bank (PDB) and PubChem (NCBI, USA). Then, drug-likeness analysis was performed on the SCFBIO web server using the Lipinski rule of five. Additionally, the binding activity and molecular interaction by PoseView web server and PyMol software v2.4.1 (Schrödinger, Inc., USA) were determined by the blind docking approach using PyRx 0.8 software. Using Lipinski's rule of five, the eighty-one bioactive chemicals in star anise were examined to see how similar they were to therapeutic compounds. The molecular docking procedure was then executed using PyMOL and PyRx 0.8 (Virtual Screening Tool) and its interaction with Mpro protein. Methylphenyl has been revealed to have the lowest binding energy for Mpro SARS-CoV-2 and great potential as an inhibitor of SARS-CoV-2 viral replication based on the comprehensive research conducted on these bioactive compounds. However, since the results are only computational, a wet lab study is required for validation. Of 38 drug-like bioactive chemicals of star anise, only methylphenyl has the lowest binding affinity, which can bind and function as inhibitor of the Mpro protease enzyme. A can obstruct the SARS-CoV-2 virus's reproduction. As a result, the SARS-CoV-2 virus cannot assemble its genetic material, capsids, and other body components. Viral replication can be stopped to lower the amount of genetic material copied from the virus.